2020
DOI: 10.1038/s41419-020-2430-3
|View full text |Cite
|
Sign up to set email alerts
|

The cellular prion protein is a stress protein secreted by renal tubular cells and a urinary marker of kidney injury

Abstract: Endoplasmic Reticulum (ER) stress underlies the pathogenesis of numerous kidney diseases. A better care of patients with kidney disease involves the identification and validation of ER stress biomarkers in the early stages of kidney disease. For the first time to our knowledge, we demonstrate that the prion protein PrP C is secreted in a conventional manner by ER-stressed renal epithelial cell under the control of the transcription factor x-box binding protein 1 (XBP1) and can serve as a sensitive urinary biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In recent years, protective functions have also been attributed to PrP in the kidney (Han et al 2020 ; Yoon et al 2021 ; Zhang et al 2015 ), and PrP is ‘secreted’ into the urine in response to chronic kidney disease and ER stress in kidney injury (Bignon et al 2020 ). However, before assessment of PrP in plasma can be used as a reliable biomarker, differentiation between sPrP and other PrP forms again seems appropriate.…”
Section: Potential Relevance Of Prp Shedding In Other Pathological Pr...mentioning
confidence: 99%
“…In recent years, protective functions have also been attributed to PrP in the kidney (Han et al 2020 ; Yoon et al 2021 ; Zhang et al 2015 ), and PrP is ‘secreted’ into the urine in response to chronic kidney disease and ER stress in kidney injury (Bignon et al 2020 ). However, before assessment of PrP in plasma can be used as a reliable biomarker, differentiation between sPrP and other PrP forms again seems appropriate.…”
Section: Potential Relevance Of Prp Shedding In Other Pathological Pr...mentioning
confidence: 99%
“…In the past, PrP C in kidney tissues has been only used as a proxy model for studying neuronal PrP C [ 66 ], which led to the current unavailability of literature dedicated towards examining the functions of PrP C in the kidneys. Given that recent studies on kidney injuries and PrP C have demonstrated that PrP C could be a reliable biomarker for renal injury [ 67 ] and protect cells against a chronic kidney disease (CKD) environment [ 68 ], further exploration of the link between various kidney diseases and endogenous PrP C is greatly merited. Throughout this review, we have summarized the current understandings of PrP C in the kidneys and its application in renal pathologies and identified potential PrP C -based therapeutic strategies for major kidney diseases, including acute and chronic kidney injury, renal fibrosis, and cancers.…”
Section: General Characteristics Of Cellular Prion Proteins In Kidneysmentioning
confidence: 99%
“…Taken together, there seems to be sufficient evidence for PrP C -mediated protection against renal IR injury, particularly through modulation of the mitochondrial function and the ERK signaling pathway ( Figure 2 B). This provides a plausible explanation for why PrP C is secreted by renal epithelial cells under endoplasmic reticulum stress [ 67 ]. The current efforts to take advantage of such protective functions of PrP C will be reviewed in the following sections.…”
Section: Physiological Functions Of Prp C In the Kidneysmentioning
confidence: 99%
See 1 more Smart Citation